2020
DOI: 10.3390/nano10040698
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Chitosan Derivatives Nanoparticles with Antiangiogenic Effect for Cancer Therapy

Abstract: Angiogenesis is a physiological process involving the growth of new blood vessels, which provides oxygen and required nutrients for the development of various pathological conditions. In a tumor microenvironment, this process upregulates the growth and proliferation of tumor cells, thus any stage of angiogenesis can be a potential target for cancer therapies. In the present study, chitosan and his derivatives have been used to design novel polymer-based nanoparticles. The therapeutic potential of these newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…Interestingly, anti-angiogenic treatments are frequently seen in literature involve the use of chemical substances, such as the chemotherapy drug doxorubicin [ 129 , 165 ] as well as thalidomide derivatives [ 59 ]. The application of nanoparticles such as gold [ 60 , 84 ], green [ 166 ], zinc tungstate [ 61 ] and chitosan derived nanoparticles [ 94 ] have high efficacy in the inhibition of blood vessel development, with significant reductions in blood vessel number, length and density reported.…”
Section: Cam Experimental Treatmentsmentioning
confidence: 99%
“…Interestingly, anti-angiogenic treatments are frequently seen in literature involve the use of chemical substances, such as the chemotherapy drug doxorubicin [ 129 , 165 ] as well as thalidomide derivatives [ 59 ]. The application of nanoparticles such as gold [ 60 , 84 ], green [ 166 ], zinc tungstate [ 61 ] and chitosan derived nanoparticles [ 94 ] have high efficacy in the inhibition of blood vessel development, with significant reductions in blood vessel number, length and density reported.…”
Section: Cam Experimental Treatmentsmentioning
confidence: 99%
“…When lung and colon cancer cell lines were exposed to Zn-BTC@CS for 24, 48, and 72 h, the number of viable cancer cells was reduced, with the most notable effect appearing against colon cancer cell lines ( Figure 5 ). Previous studies declared that chitosan-derivative-based nanostructures showed markedly increased therapeutic impact compared to chitosan alone [ 45 ]. The MTT test showed the toxic effect of Zn-BTC@CS, as it inhibited the proliferation of A549 and DLD-1 cancer cell lines in a dose-dependent manner with IC 50 values of 13.2 and 19.8 µg/mL for the colon and lung cancer cell lines, respectively ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of the study, they established that copper increases angiogenesis by increasing HIF-1α / VEGF expression [23]. As a result of our literature review about chitosan, we encountered a manuscript by Dragostin et al They demonstrated the anti-angiogenic effect of chitosan nanoparticles in CAM assay [22]. In another study, Ribeiro and colleagues have shown that insulin-containing chitosan nanoparticles stimulate angiogenesis [24].…”
Section: Discussionmentioning
confidence: 95%
“…Chitosan has been shown to inhibit angiogenesis in chick embryo chorioallantoic membrane (CAM) models [22].…”
Section: Discussionmentioning
confidence: 99%